(3GdEYdGe HCYdGe HjJ GGddg GdMQGes - (3eMeO Hf CMeO Hf eMeO Hf bGVj NGf eMehO GdfgQhGdj GdMfaj Gdecj , bWH GdOjf,J (B988 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdeSLO efkG heJGHI ddfGS CeG HYO adeG habfi Gddg JYGdi dNOeI GdYde GdTQja JThbJ faSi Edi GdEWdGY Ydi Yde GdGKGQ , hJThbJ Edi af GdJGQjN hYde GdCNHGQ s
(3BNQgG (B:s
(3hbO QCjJ Cf CLYd NJGe GdcJGH eSckG aCNJeg ceG HOCJg HGdOYGA dOhGe SdWGffG GdCYXe hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3Ydi GdfSNI JedcGJ eMOKI CbOegG SfI (B1260 (3g`s
(3cJHJ GdYfGhjjf hGdJhGQjN HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs